An ionic liquid supported CeO2 nanoparticlesâcarbon nanotubes composite-enhanced electrochemical DNA-based sensor for the detection of Pb2+ - Yan Li; Xiao-Rong Liu; Xiao-Hui Ning; Can-Can Huang; Jian-Bin Zheng; Jun-Cai Zhang (Elsevier, 2011)
An electrochemical sensor incorporating a signal enhancement for the determination of lead (II) ions (Pb2+) was designed on the basis of the thrombin-binding aptamer (TBA) as a molecular recognition element and ionic liquid supported cerium oxide (CeO2) nanoparticlesâcarbon nanotubes composite modification. The composite comprises nanoparticles CeO2, multi-wall carbon nanotubes (MWNTs) and hydrophobic room temperature ionic liquid (RTIL) 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4). The electrochemical sensors were fabricated by immersing the CeO2âMWNTsâEMIMBF4 modified glassy carbon electrode (GCE) into the solution of TBA probe. In the presence of Pb2+, the TBA probe could form stable G-quartet structure by the specific binding interactions between Pb2+ and TBA. The TBA-bound Pb2+ can be electrochemically reduced, which provides a readout signal for quantitative detection of Pb2+. The reduction peak current is linearly related to the concentration of Pb2+ from 1.0Ã10â8Â M to 1.0Ã10â5Â M with a detection limit of 5Ã10â9Â M. This work demonstrates that the CeO2âMWNTsâEMIMBF4 nanocomposite modified GCE provides a promising platform for immobilizing the TBA probe and enhancing the sensitivity of the DNA-based sensors. Keywords: Electrochemical, DNA-based sensor, Lead (II) ion, Ionic liquid, CeO2 nanoparticle, Multi-wall carbon nanotubes